Online GNSS processing as alternatives to different geodetic applications - Moya-Zamora, Jorge; Bastos-Gutiérrez, Sara (Uniciencia, 2015)
In this study a description in terms of utilization, throughput, file types and results of a series of online programs for GNSS data processing is done. At present the information that can be obtained from the GNSS systems, allows a diverse range of applications, from vehicle navigation to different studies related to terrestrial dynamics. The possibilities for use in geodesy rely exclusively on high accuracy that can be obtained by making the processing of GNSS data for scientific programs such as GAMIT and Bernese or a relative or differential work. However, they have developed a number of programs available online that provide a very suitable option for obtaining, in a short time solutions with acceptable accuracy for many tasks related to mapping, surveying, cadastre and geodesy. Some of these programs are based on technique Precise Point Positioning (PPP). The comparative study looked at a number of observation files in RINEX format were processed online programs APPS, CSRS, AUSPOS, OPUS and SCOUT. The results were analyzed in comparison with themselves, high accuracy positions given by Geocentric Reference System for the Americas ( SIRGAS ) ETCG station in addition to contemplate different satellite orbits files and processing mistakes online. Respect to alignment of the solutions according to the international framework lowest values were measured at 20 mm in the horizontal part.